Flow behavior, mixing and mass transfer in a Peirce-Smith converter using physical model and computational fluid dynamics - Chibwe, Deside Kudzai (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2011.